Does Dummy Food Display Effect on Food Purchase Decisions? (A Case Study of Coco Ichibanya Neo Soho Jakarta) - Ni Made Dwiyana Rasuma Putri; Reni Sulistiyowati; Pamela (The Postgraduate School of Tourism Sahid Polytechnic, 2022)
ABSTRACT Purpose: This research aims to determine the effect of dummy food displays on the food purchasing decision at Coco Ichibanya Neo Soho, West Jakarta, Indonesia. Research methods: This research has a dummy food display as an independent variable and a purchasing decision as to the dependent variable. The measurement of variables used in this research is a Likert scale. The population is consumers who have visited Coco Ichibanya Neo Soho West Jakarta. This research used 96 respondents who were sampled because they met the specified criteria. The accidental sampling method is the method applied in this research. This research used questionnaires as primary data and websites, journals, books, and others related to the research as secondary data. The analyzing method used in this research is a simple regression test method with the help of an SPSS 25 computerized program. Results and discussion: The validity test results state the dummy food display (0.368-0.662 > 0.1) and purchasing decisions (0,400-0,621 > 0.1) so that it is claimed as valid. T-test results conclude that the dummy food display has a positive effect on purchasing decisions because the significance value of 0,000 is less than the value of 0.05. Implication: The dummy food display has a positive and significant effect on purchasing decisions. It can be useful to answer the problem regarding the purchasing decision of Coco Ichibanya Neo Soho based on the dummy food display. Keywords: product display, dummy food display, purchase decision.